Using Picture Series to enhance students’ ability in narrative writing - Khotimah Khotimah; Bukhari Daud; Burhansyah Burhansyah (Research in English and Education Journal, 2017)
The objective of this study is to figure out whether the use of picture series can improve students’ ability in narrative writing skill, especially on the content aspect of the third grade students at MTsN Rukoh Banda Aceh. Most of the third grade students at MTsN Rukoh Banda Aceh felt difficult to generate and develop their ideas in writing form. By this reason, the researcher conducted experimental-quantitative research with the pre-test and post-test control group design to the students by using picture series to help them improve their writing. The samples of this study were class XI–1 as the experimental class and class XI-5 as the control class, which were chosen by using random sampling. In this study, the data was collected by means of writing test, consisting of pre-test and post-test. The result of this study showed that the improvement of the experimental class was higher than that of the control class. It was known from the comparison of the improvement of their average score in both classes on the content aspect of writing that is 7.26 in the experimental class and 3.28 in the control class. Besides, the result of the hypothesis testing shows that the score is 0.000 which is lower than 0.05 (0.0000.05), which means the research hypothesis that “the use of picture series can improve the students’ ability in narrative writing skill especially on the content aspect” is accepted.